How health beliefs and sense of control predict adherence to COVID-19 prevention guidelines among young adults in South Korea - Lee, Gayeon; Park, Soo Hyun (Frontiers in Psychology, 2022)
This study defined adherence to COVID-19 prevention guidelines as health behavior and examined whether the two constructs of the health belief model (i.e., perceived susceptibility and perceived severity) and sense of control predict the level of adherence among young adults in South Korea. An online survey (N = 200) conducted in June 2021, showed that perceived susceptibility, perceived severity, and sense of control positively predict adherence behavior. Sense of control significantly moderated the relationship between perceived susceptibility and adherence even after controlling for depression and perceived health status. Specifically, individuals with a lower level of perceived susceptibility still adhered to COVID-19 prevention guidelines if they had a higher level of sense of control. The finding demonstrates the key role of sense of control in promoting adherence to COVID-19 prevention guidelines and the relationship between sense of control and two constructs of the health belief model. Implication for public messaging targeted at young adults during pandemic situations is also discussed.